Legal Reform for Victims in Criminal Justice System of Indonesia and Russian Juridical Review - Wulandari, Cahya; Masyhar, Ali; Hassan, Muhamad Sayuti (Journal of Law and Legal Reform, 2024)
The realization of justice in a criminal process cannot be separated from the position of the victim in the criminal justice system. Victims as parties directly dealing with criminal acts certainly expect their rights and interests to be properly accommodated. This article is written based on a method of normative juridical research with a comparative approach in victim protection regulation in Russia and Indonesia. In the process of resolving criminal cases through the criminal justice system in Indonesia, the victim's interests are represented by the Public Prosecutor so that they do not have access to have their wishes heard further. Even though in Law Number 1 of 2023 concerning the Criminal Code, sentencing guidelines and purposes of sentencing have been regulated, which in this case requires the role of the victim and/or their family, and further regulation is needed in practice. This is of course very different from the position of the victim in the Criminal Procedural Code in Russia, which places the victim actively in the process of the criminal justice system. The presence of the prosecutor in court does not diminish the victim's right to fight for their rights, including by conducting private prosecution of the perpetrator in the form of material or immaterial compensation. To be able to realize the values contained in Pancasila which are not only as Grundnorm but also as Grundwerten, it is necessary to place this victim in the process of resolving criminal cases at every level in the criminal justice system